Clinical characteristics of eosinophilic asthma exacerbations. Issue 2 (21st September 2016) - Bjerregaard, Asger; Laing, Ingrid A.; Backer, Vibeke; Fally, Markus; Khoo, Siew‐Kim; Chidlow, Glenys; Sikazwe, Chisha; Smith, David W.; Le Souëf, Peter; Porsbjerg, Celeste
ABSTRACT: Background and objective: Airway eosinophilia is associated with an increased risk of asthma exacerbations; however, the impact on the severity of exacerbations is largely unknown. We describe the sputum inflammatory phenotype during asthma exacerbation and correlate it with severity and treatment response. Methods: Patients presenting to hospital with an asthma exacerbation were recruited during a 12‐month period and followed up after 4 weeks. Induced sputum was collected at both visits. Patients underwent spirometry, arterial blood gas analysis, fractional exhaled nitric oxide analysis, white blood cell counts and a screening for common respiratory viruses and bacteria. An eosinophilic exacerbation (EE) was defined as having sputum eosinophils ≥ 3% and a non‐eosinophilic exacerbation as < 3% (NEE). Results: A total of 47 patients were enrolled; 37 (79%) had successful sputum induction at baseline, of whom 43% had sputum eosinophils ≥3% (EE). Patients with EE had a significantly lower forced expiratory volume in 1 s (FEV1 ) % predicted (70.8%, P = 0.03) than patients with NEE (83.6%). Furthermore, EE patients were more likely to require supplemental oxygen during admission (63% vs 14%, P = 0.002). The prevalence of respiratory viruses was the same in EE and NEE patients (44% vs 52%, P = 0.60), as was bacterial infection (6% vs 14%, P = 0.44). Fractional expiratory nitric oxide (FeNO) correlated with sputum %‐eosinophils (ρ = 0.57, P < 0.001), and predicted airway eosinophilia with a sensitivity of 86% and a specificity of 70%. Conclusion: Our findings suggest that eosinophilic asthma exacerbations may be clinically more severe than NEEs, supporting the identification of these higher risk patients for specific interventions. Abstract : Patients with airway eosinophilia during an exacerbation of asthma had lower forced expiratory volume in 1 s (FEV1 ) and were more likely to require supplemental oxygen during admission than those without eosinophilia. This suggests that eosinophilic asthma exacerbations are more severe than non‐eosinophilic exacerbations.